Philosophy of Climate Science Part I: Observing Climate Change. Issue 12 (December 2015) - Frigg, Roman; Thompson, Erica; Werndl, Charlotte
Abstract: This is the first of three parts of an introduction to the philosophy of climate science. In this first part about observing climate change, the topics of definitions of climate and climate change, data sets and data models, detection of climate change, and attribution of climate change will be discussed.